Effect of synthetic colloidal nanoparticles in acrylic resin of dental use. (March 2019) - Souza Neto, Francisco Nunes de; Sala, Renata Lang; Fernandes, Renan Aparecido; Oliveira Xavier, Tatielih Pardim; Cruz, Sandra Andrea; Paranhos, Caio Marcio; Monteiro, Douglas Roberto; Barbosa, Debora Barros; Delbem, Alberto Carlos Botazzo; Camargo, Emerson Rodrigues de
Graphical abstract: Highlights: Advanced Ag-based acrylic resins for prosthesis users is proposed. Thermo-mechanical behavior of acrylic resins is influenced by Ag nanoparticles. Concentration and distribution of Ag nanocomposites regulate biofilm formation. Abstract: Acrylic resin employed in dental materials can act as substrate for microorganisms' adhesion and biofilm formation. To overcome this, silver nanoparticles (AgNPs) were combined with poly(methyl methacrylate) (PMMA) to reduce denture stomatitis caused by Candida glabrata . Although AgNPs antimicrobial activity is already known, the physicochemical properties of its nanocomposites, which dictate the performance of these commercial targets remain little explored. We evaluated the effect of different amount of AgNPs in PMMA obtained by the thermal polymerization. Among the mechanical tests employed, PMMA flexural strength decreased with higher AgNPs concentration. The microbiological adhesion test against Candida glabrata revealed the nanocomposite with 0.05% of AgNPs has greater capacity to inhibit the biofilm formed on its surface. Although we observed distinct thermo-mechanical behavior in the presence of AgNPs, antimicrobial property was not linearly dependent of nanoparticles concentration and was influenced by nanoparticles dispersion and distribution in the polymer matrix.